Advancing studies on global biocrust distribution - S. Wang; S. Wang; L. Ma; L. Ma; L. Yang; L. Yang; Y. Ma; Y. Ma; Y. Zhang; Y. Zhang; C. Zhao; C. Zhao; et al. (SOIL, 2024)
Biological soil crusts (biocrusts hereafter) cover a substantial proportion of the dryland ecosystem and play crucial roles in ecological processes such as biogeochemical cycles, water distribution, and soil erosion. Consequently, studying the spatial distribution of biocrusts holds great significance for drylands, especially on a global scale, but it remains limited. This study aimed to simulate global-scale investigations of biocrust distribution by introducing three major approaches, namely spectral characterization indices, dynamic vegetation models, and geospatial models, while discussing their applicability. We then summarized the present understanding of the factors influencing biocrust distribution. Finally, to further advance this field, we proposed several potential research topics and directions, including the development of a standardized biocrust database, enhancement of non-vascular vegetation dynamic models, integration of multi-sensor monitoring, extensive use of machine learning, and a focus on regional research co-development. This work will significantly contribute to mapping the biocrust distribution and thereby advance our understanding of dryland ecosystem management and restoration.